Preparation and Evaluation of Ciprofloxacin Hydrochloride Floating Oral Delivery System (Biological Sciences - PJSIR, 2008)
A sustained release system for ciprofloxacin hydrochloride designed to increase its residence time in the stomach was achieved through the preparation of floating microparticles by the solvent diffusion technique, using Eudragit S 100 and Eudragit RL 100 polymers. Eight different ratios of Eudragit mixture were used for the formula- tion, all of which showed good flow properties and packability. The drug retained in the microparticles decreased with increase in Eudragit RL 100 content, whereas, the floating ability increased with increase in weight ratio of Eudragit RL 100. There were differences between the formulations as to their appearance and size distribution. Fourier trans- form infrared (FTIR) spectrophotometeric study confirmed intactness of drug in formulations. The formulation containing ES: ERL in a ratio1.5:1 exhibited high percentage of floating particles with a controlled release of drug in 0.1N HCl.